Pendampingan Lingkungan Aman Untuk Anak bagi Ibu-Ibu Anggota Majelis Ta’lim Al Yamin Citeras Rangkasbitung Lebak Banten - Siti Wardah Rizkiah; Resi Dazia (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
This community outreach program aims to increase awareness and the role of parents, particularly mothers, in creating a safe, friendly, and supportive environment for children's growth and development. This outreach program is motivated by the increasing risk of violence and neglect against children in the family and community. The methods used include a participatory approach through counseling and outreach. The results of the program indicate that participants experienced an increased understanding of the concept of a child-friendly environment and strategies for preventing and addressing it within the family environment. This activity also fostered a collective commitment among mothers to monitor each other and create a safer social space for children